2020
DOI: 10.1016/j.dcn.2020.100818
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modulation of frontal theta power predicts cognitive ability in infancy

Abstract: Highlights This longitudinal infant study found that frontal theta power increased over the course of video viewing in 6-month-olds. Individual differences in frontal theta power change at 6-months-old significantly predicted non-verbal cognitive ability. Individual differences in frontal theta power change at 6 months was not associated with executive function at 9 months. Frontal theta change at 6 months may be an early indicator of la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 51 publications
6
28
0
Order By: Relevance
“…Specifically, we focused on EEG theta power. Infant theta oscillations have been associated with infant attention in a number of studies [ 66 , 69 , 70 , 71 , 72 ], and maternal ADHD symptoms are related to higher mean infant theta power [ 73 ]. In this study we investigated both mean frontal theta and dynamic changes in frontal theta.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we focused on EEG theta power. Infant theta oscillations have been associated with infant attention in a number of studies [ 66 , 69 , 70 , 71 , 72 ], and maternal ADHD symptoms are related to higher mean infant theta power [ 73 ]. In this study we investigated both mean frontal theta and dynamic changes in frontal theta.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether midfrontal theta power supports conflict monitoring in children the way that it does later in development. However, it relates to cognitive performance more generally (in contexts other than the flanker task) from infancy on (e.g., Braithwaite et al, 2020;Canen & Brooker, 2017;Uhlhaas et al, 2009). As functional connectivity both between the cingulo-opercular (including ACC) and frontoparietal (including lateral PFC) networks, and within each network, increases during childhood and adolescence (Baum et al, 2017;Fair et al, 2008;Luna et al, 2015), it is possible that more mature patterns of theta oscillations support growing efficiency in conflict monitoring and better signal the need for more control over sensory information processing.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al (2020) reported that EEG theta change in infancy during the presentation of dynamic movies of people and objects is a predictive biomarker for later cognitive deficits, particularly in high-risk populations. Braithwaite et al (2020) also found increases in the theta wave recorded at 6month-old infants at low-risk while presenting the non-social video. These changes in theta significantly predicted non-verbal cognitive ability measured at age 9-months.…”
Section: Discussionmentioning
confidence: 65%